Does whole-body vibration potentiate reactive strength performance in sprinters? - Washif, J. A. (Journal of Australian Strength and Conditioning, 2019)
Inclusion of whole-body vibration within a realistic warm-up has no positive effect on reactive strength performance beyond that caused by warm-up alone, however, case-by-case basis is recommended when applying whole-body vibration to enhance reactive strength performance.